Identification and Expression Pattern of EZH2 in Pig Developing Fetuses. (6th October 2020) - Tan, Baohua; Hong, Linjun; Qiao, Jiaxin; Zhou, Jian; Xing, Pingping; Yan, Guanhao; Zheng, Enqin; Cai, Gengyuan; Huang, Sixiu; Wu, Zhenfang; Gu, Ting
Abstract : The proper methylation status of histones is essential for appropriate cell lineage and organogenesis. EZH2, a methyltransferase catalyzing H3K27me3, has been abundantly studied in human and mouse embryonic development. The pig is an increasing important animal model for molecular study and pharmaceutical research. However, the transcript variant and temporal expression pattern of EZH2 in the middle and late porcine fetus are still unknown. Here, we identified the coding sequence of the EZH2 gene and characterized its expression pattern in fetal tissues of Duroc pigs at 65- and 90-day postcoitus (dpc). Our results showed that the coding sequence of EZH2 was 2241 bp, encoding 746 amino acids. There were 9 amino acid insertions and an amino acid substitution in this transcript compared with the validated reference sequence in NCBI. EZH2 was ubiquitously expressed in the fetal tissues of two time points with different expression levels. These results validated a different transcript in pigs and characterized its expression profile in fetal tissues of different gestation stages, which indicated that EZH2 played important roles during porcine embryonic development.